Song of The Beast - Berg, Carol (New York A Roc Book, 2011)
"Brutal imprisonment has broken Aidan McAllister. His celebrated voice is silent. His hands ruined. His music is destroyed, and with it the visions he once gave a kingdom ravaged by dragon war. The god who nurtured his talent since boyhood has abandoned him. All he wants to do is hide. But no one ever told Aidan his crime. And when pursuers threaten to throw him back in the prison he's just left, he's driven to discover the truth, risking his hard-bought freedom to unlock the mind of his god and the heart of his enemy"--Page 4 of cover.
Keywords: Fantasy fiction -- Courage -- Dragons